HUMAN RIGHTS AS A FUNDAMENTAL VALUE IN UKRAINIAN SOCIETY - Pylgun, Nataliia; Plys, Nataliia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: the article reveals the elements of the legal essence of a person in the recognition of his dignity, equal and inalienable human rights, which are the basis of freedom, justice and universal peace. The study presents the significant, fundamental possibilities of the standard of living of a person in the conditions of war in Ukraine; facts that testify to the violation of human rights and freedoms in Ukraine. Research methods: dialectical method of cognition, historical and general scientific methods. The basis of the methodology is a systematic approach that allows considering a certain object as a multifaceted phenomenon. Results: the concept of human rights and their implementation in the conditions of war, the guarantee of human rights by the state and their compliance with international standards and requirements of international law are defined. The authors state that human rights in Ukraine are clearly defined in the Constitution, but in connection with the invasion of the russian federation on the territory of the Ukrainian state, their violation has been recorded, which causes restrictions on the rights and freedoms of Ukrainian citizens. To date, gross violations of human rights have been recorded, such as: encroachment on human life and health, mass destruction of the civilian population, murders of Ukrainian leaders, violence, torture, seizure and damage to property; freedom of movement, the right to personal and private life and many other criminal actions by the aggressor were violated. Currently, all facts of criminal acts are recorded by international and national organizations; at the same time, the world community recognized that the events taking place on the territory of Ukraine are a genocide of the Ukrainian people. In general, there are national and international guarantees of human rights, where the main task is the formation of a mechanism for ensuring and protecting human rights, which includes a general system of guarantees of rights and freedoms. At the same time, human rights correspond to the obligations of the state regarding respect for human rights, their provision and protection of human life. Therefore, within the framework of the human rights mechanism, Ukraine should develop draft laws that will regulate human rights during the period of martial law.